Investigating Metacognitive, Affective , and Social strategies on Students’ speaking Proficiency - Siti Nandiah; Abdul Muin Abdul; Anita Anita (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2025)
This study aims to investigate the levels and impacts of indirect learning strategies—metacognitive, affective, and social—on students' speaking proficiency, based on Rebecca Oxford’s theory. The research employs a descriptive qualitative design, utilizing a combination of closed-ended questionnaires, semi-structured interviews, and documentation to gather data from 15 third-semester students. The Strategy Inventory for Language Learning (SILL) is used to assess the levels of strategy use, while interviews provide deeper insights into the strategies' impacts on speaking proficiency. To verify the accuracy of the data, the study also applies triangulation methods. The results reveal that the majority of students exhibit high levels of metacognitive, affective, and social strategy use, which positively correlate with improvements in speaking proficiency. Specifically, students who demonstrated high levels of strategy use showed enhanced pronunciation, grammar, vocabulary, confidence, and emotional regulation, leading to better speaking outcomes. In contrast, students with lower levels of strategy use faced challenges in speaking proficiency, particularly due to anxiety and low self-confidence.